Analisis Pengaruh Indeks Pembangunan Manusia terhadap Tingkat Kemiskinan di Kabupaten Lembata, Provinsi Nusa Tenggara Timur - Joseph Emiliano Junior; Joko Priyono (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
The purpose of this study was to evaluate the impact of the Human Development Index (HDI) on poverty levels in Lembata Regency, East Nusa Tenggara Province. The research data were secondary data from the Central Statistics Agency and local government agencies. The analysis method used multiple linear regression analysis to measure the influence of each HDI component—namely life expectancy, education level, and decent standard of living on poverty. The research findings showed that the components of life expectancy and education did not have a significant impact on poverty, while decent standard of living was proven to have a significant impact on reducing poverty levels. Based on the determination coefficient test, this research model can explain around 61.5% of the variation in poverty. Overall, although there is a significant influence from several variables, the simultaneous influence of the three HDI indicators on poverty doesn’t significant.